2019
DOI: 10.1155/2019/7816491
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Trap Components Associate with Infarct Size, Ventricular Function, and Clinical Outcome in STEMI

Abstract: Background The relevance of neutrophil extracellular traps (NETs) in acute ST-elevation myocardial infarction (STEMI) is unclear. We explored the temporal profile of circulating NET markers and their associations to myocardial injury and function and to adverse clinical events in STEMI patients. Methods and Results In 259 patients, blood samples were drawn before and after PCI, on day 1, and after 4 months. Double-stranded deoxyribonucleic acid (dsDNA) and myeloperoxidase-DNA (MPO-DNA) were measured in serum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Nonetheless, the lack of a clear association with TnT may indicate that the measured dsDNA has not merely leaked from damaged cardiomyocytes. This is corroborated by our previous observation that dsDNA peaked prior to PCI, indicating the importance of temporality which this study could not assess 25 . Even though causality cannot be established from our observations, and there is incongruence between the NETs-specific components, multivariable analyses show that even after adjusting for variables related to myocardial injury and function such as TnT and NT-proBNP, dsDNA still confers an increased risk of death.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, the lack of a clear association with TnT may indicate that the measured dsDNA has not merely leaked from damaged cardiomyocytes. This is corroborated by our previous observation that dsDNA peaked prior to PCI, indicating the importance of temporality which this study could not assess 25 . Even though causality cannot be established from our observations, and there is incongruence between the NETs-specific components, multivariable analyses show that even after adjusting for variables related to myocardial injury and function such as TnT and NT-proBNP, dsDNA still confers an increased risk of death.…”
Section: Discussionsupporting
confidence: 89%
“…NETs dominate the acute inflammatory setting of STEMI ( Mangold et al, 2015 ; Helseth et al, 2019 ). We reported that besides their cytotoxic ( Saffarzadeh et al, 2012 ) and pro-thrombotic ( Fuchs et al, 2012 ) properties, the presence of NETs affects other cell types such as fibrocytes ( Hofbauer et al, 2019 ) and monocytes ( Mangold et al, 2019 ) that are recruited to the culprit site and the ischemic myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…NET burden was associated with microvascular obstruction, myocardial salvage index, and left ventricular ejection fraction in STEMI patients (Helseth et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Aside from expulsion of reactive oxygen species and other proteins, neutrophils also release extracellular traps (NETs), appearing as extracellular clouds consisting of deoxyribonucleic acid (DNA), histones, and neutrophil granule proteins in response to stimuli such as activated platelets or IL-8 [ 7 ]. NETs have been shown to be cytotoxic, proinflammatory and prothrombotic, potentially augmenting myocardial injury [ 8 , 9 ], and have recently been suggested to affect both myocardial infarct size and post-MI left ventricular remodeling [ 10 , 11 ]. However, the contribution of NETs components with respect to AHF complicating MI has not previously been reported on.…”
Section: Introductionmentioning
confidence: 99%